The effect of Electronic Hand Hygiene Monitoring Towards Hand Hygiene Compliance: A Literature Review - Annisa Rahmi Galleryzki; Hanny Handiyani (Alta Dharma Publisher, 2020)
Hand Hygiene (HH) is the most effective step to reduce the transmission rate of patient care infections. Attempting to increase HH is carried out by using technology and handwashing compliance as an indicator of its success. The study aimed to describe information on technological developments in HH monitoring in hospitals and their effects on the level of compliance of health workers, especially nurses, in conducting HH. This study uses the literature review method, using the Science Direct, Scopus, Ebsco, and PROQUEST databases. The author uses keywords: